Emergency airway management by non-anaesthesia house officers—a comparison of three strategies. Issue 2 (1st March 2001) - Dörges, V; Ocker, H; Wenzel, V; Sauer, C; Schmucker, P
Abstract : Objectives —The purpose of this study was to determine effects of different airway devices and tidal volumes on lung ventilation and gastric inflation in an unprotected airway. Methods —Thirty one non-anaesthesia house officers volunteered for the study, and ventilated a bench model simulating an unintubated respiratory arrest patient with bag-valve-facemask, laryngeal mask airway, and combitube using paediatric and adult self inflating bags. Results —The paediatric versus adult self inflating bag resulted with the laryngeal mask airway and combitube in significantly (p<0.001) lower mean (SEM) lung tidal volumes (376 (30) v 653 (47) ml, and 368 (28) v 727 (53) ml, respectively). Gastric inflation was zero with the combitube; and 0 (0) v 8 (3) ml with the laryngeal mask airway with low versus large tidal volumes. The paediatric versus adult self inflating bag with the bag-valve-facemask resulted in comparable lung tidal volumes (245 (19) v 271 (33) ml; p=NS); but significantly (p<0.001) lower gastric tidal volume (149 (11) v 272 (24) ml). Conclusions —The paediatric self inflating bag may be an option to reduce the risk of gastric inflation when using the laryngeal mask airway, and especially, the bag-valve-facemask. Both the laryngeal mask airway and combitube proved to be valid alternatives for the bag-valve-facemask in this experimental model.